“Data Free Flow with Trust”: Japan’s struggle to integrate democracy and human rights into digital trade policy - Dale, John G.; Aizawa, Nobuhiro (Frontiers in Sociology, 2024)
A powerful regime for regulating trade, the Group of Seven (G-7) has increasingly negotiated its digital trade through bilateral and preferential trade agreements, including with non-member states in the Global South. Focusing on the dominant concept shaping these agreements, Japan’s “Data Free Flow with Trust” (D.F.F.T.), we trace its discursively contested emergence and meaning within a national (“Society 5.0”) vision for Japan’s digital transformation, and its subsequent transnationalization in international fora and institutionalization in global digital trade policy. Drawing on our interviews with Japanese government ministers, business elites, and legal experts who contributed to the processual development of D.F.F.T., as well as diverse additional primary sources, we find that the D.F.F.T. has become more than a trade policy, covering a wider range of social and geopolitical issues. In particular, we show that contention over “data localization measures” has restructured international relations of trust, especially across the Global North/South divide. Ultimately, this research report contributes to our understanding of how D.F.F.T. poses threats to human rights, democracy, and the global knowledge economy that may undermine its goals of enhancing innovation capacity and economic growth.